Analyzing the Performance of Machine Learning Algorithms in Pricing Financial Options: A Study on the Tehran Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This study compares the performance of machine learning algorithms with the Black-Scholes model in predicting the price of financial options. Data from 153 contracts traded on the Tehran Stock Exchange between April 2018 and July 2024 were used. The models' performance was evaluated using MAE and RMSE metrics, and the results indicated that machine learning algorithms significantly outperformed the Black-Scholes model in terms of prediction accuracy.